Melting the Clock: Dalian Concepts of Temporality and Pedagogical Documentation in Early Childhood Education - Bjartveit, Carolyn (Journal of Childhood Studies, 2025)
The author describes how her documentation of children’s play experiences and the stories that preschool children have told her continue to be useful and are reinterpreted in her current work with postsecondary teacher education programs. She explains the documentation as a resource for sparking fictional story writing, play, and critical dialogue about teaching and learning in early childhood education settings. Salvador Dali’s artistic representations of time and Hans-Georg Gadamer’s philosophical concepts of temporal distance and the movement of play provide a framework for understanding the long-lasting value and timelessness of pedagogical documentation in supporting inquiry-based learning and play (pre-K to postsecondary levels).